AS EMOÇÕES E TRANSTORNO DO ESPECTRO AUTISTA (TEA): PERCEPÇÕES DE PROFESSORES EM FORMAÇÃO (REMUNOM, 2025)
This study analyzes how teachers in training perceive the emotions of students with Autism Spectrum Disorder (ASD), with the aim of promoting a more empathetic and safe school inclusion. Understanding emotions is essential in Inclusive Education, as it enables teachers to better meet the socio-emotional needs of autistic students. With the increased inclusion of neurodivergent students in mainstream classes, it is crucial to prepare future teachers to deal with this diversity, strengthening empathy and benefiting the school community. The research was based on a literature review, using sources such as Google Scholar, Scielo and CAPES Platform, focusing on emotions, cognition and behavior in ASD, from a neurobiological perspective. The state of the art on teachers' perceptions of emotions in autism was also reviewed, considering publications from 2013 onwards, after Law No. 12.764/2012, which guarantees the right of autistic people to mainstream education. In addition, field research was carried out with 18 Biological Sciences students from UERJ/FFP, who answered a questionnaire via Google Forms. The qualitative data indicated that teachers in training face challenges in identifying and understanding the emotions of students with ASD, highlighting a gap in training to deal with these emotional complexities. This result highlights the need to reformulate teacher training curricula, including modules on emotional recognition and management of social interactions, especially from an inclusive perspective. The study hope to inspire pedagogical practices and training policies, promoting an inclusive and emotionally safe school environment for all involved.